THE GROWING ROLE OF THE BH3 MIMETIC DRUG VENETOCLAX IN THE THERAPY OF ACUTE MYELOID LEUKEMIA - Elvira Pelosi; Germana Castelli; Ugo Testa (Mediterranean Journal of Hematology and Infectious Diseases)
In spite recent progresses, acute myeloid leukemia (AML) remains a disease associated with poor prognosis, particularly in older AML patients unfit to tolerate intensive chemotherapy treatment. The development and introduction in therapy of the drug Venetoclax, a potent BH3 mimetic targeting the antiaopoptotic protein BCL-2, inducing apoptosis of leukemic cells, has shown to be a promising treatment for newly diagnosed, relapsed and refractory AML patients ineligible for induction chemotherapy. Combination treatments using Ventoclax and a hypomethylating agent (azacytidine or decitabine) or low-intensity chemotherapy have shown in newly diagnosed patients variable response rates, with highly responsive patients with NPM1, IDH1-IDH2, TET2 and RUNX1 mutations and with scarcely responsive patients with FLT3, TP53 and ASXL1 mutations, complex karyotypes and secondary AMLs. Patients with refractory/relapsing disease are less responsive to Venetoclax-based regimens.